The deerslayer, or, The first war-path - Cooper, James Fenimore, 1789-1851 (State University of New York Press, 1987)
Natty Bumppo, a young white hunter brought up in the Delaware Indian tribe, has to defend settlers before returning to the Iroquois who have allowed him parole.
Keywords: Bumppo, Natty -- (Fictitious character) -- Fiction.; Bumppo, Natty -- (Fictitious character); Frontier and pioneer life -- New York (State) -- Fiction.; Delaware Indians -- Fiction.; Iroquois Indians -- Fiction.; United States -- History -- French and Indian War, 1754-1763 -- Fiction.; Iroquois -- Romans, nouvelles, etc.; États-Unis -- Histoire -- 1754-1763 (Guerre de Sept Ans) -- Romans, nouvelles, etc.; FICTION -- Historical.; Delaware Indians; Frontier and pioneer life; Iroquois Indians; New York (State); United States; 1754-1763; War stories.; War stories; Historical fiction; History; Fiction; Historical fiction.